Europa Proyecciones y percepciones históricas (UNIVERSIDAD DE SALMANCA, 1997)
CONTENIDO : VACA LORENZO, A.; TAMAMES, R.; ISLA FREZ, A.; FERNANDEZ CONDE, J.; VIGUERA MOLINS, M.J.; BOUZA, F.; ALVAREZ DE MIRANDA, P.; GARCIA JORDAN, P.; ADAO DA FONSECA, L.; PEREZ DELGADO, T.; TAIBO ARIAS, C.